Analisis Pelaksanaan Discharge Plannning Terhadap Tingkat pengetahuan Pasien Typhoid Fever di Rumah Sakit: Sudi Kasus - Risma Dian Ayu; Nurfika Asmaningrum; Retno Purwandari; Ika Mardiyah Bratajaya (Health and Technology Journal (HTechJ), 2025)
Discharge planning is essential for providing special education or training to patients and their families when a patient is admitted to the hospital and prepares for discharge. It is a crucial part of nursing care that requires collaboration across multiple disciplines. The goal of discharge planning is to facilitate communication between nurses and patients, enabling the provision of procedures for managing and preventing diseases at home. Typhoid fever, an endemic infectious disease, necessitates continued care and treatment. The ability of nurses to effectively implement discharge planning significantly enhances families' understanding and capacity to care for patients with typhoid fever. This study analyzes the implementation of discharge planning for patients with typhoid fever at Treatment Room D of Kaliwates General Hospital in Jember. This case report examines the discharge planning process for these patients. To assess changes in understanding disease prevention, the study measured patients' knowledge before and after implementing discharge planning using a questionnaire on understanding typhoid disease. The results indicate that implementing discharge planning effectively improves patients' understanding of disease prevention related to typhoid fever. Before discharge planning was instituted, patients scored an average of 50% on the pretest regarding their knowledge. After the discharge planning was carried out, the posttest score increased to 90%. This demonstrates that providing discharge planning to families and patients significantly enhances their knowledge about typhoid fever.